ANALISIS PENGARUH KOMPENSASI FINANSIAL DAN NONFINANSIAL TERHADAP KINERJA PEGAWAI PADA KANTOR BADAN KEPEGAWAIAN DAN PENGEMBANGAN SUMBER DAYA MANUSIA KOTA BAUBAU - Nasriah Akil (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2018)
This study aims to determine the Effect of Financial and Nonfinancial Compensation on Employee Performance at Human Resources Agency and Human Resource Development Office of Baubau City. Based on the results of analysis and discussion that have been stated previously, the authors conclude that Financial Compensation and Non-Financial Compensation simultaneously have a significant effect on Employee Performance at the Office of BKP Human Resources Baubau City with a singnifikansi level of (0,042). Partially Financial Compensation affects the significance of Employee Performance with singnificancy level of (0,038) whereas Non-Financial Compensation influences No significancy to Employee Performance with Value significancynya (0,161).